2015
DOI: 10.12659/ajcr.892527
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Incomplete Fusion of Superior Mesenteric Artery Mimicking Dissection

Abstract: Patient: Male, 62Final Diagnosis: Superior mesenteric artery anatomic variantSymptoms: Abdominal pain • diarrhea • transcient ischemic attacksMedication: —Clinical Procedure: CT of abdomen and pelvisSpecialty: SurgeryObjective:Congenital defects/diseasesBackground:Both spontaneous SMA dissection and anatomical variants of GIT vasculature are well known entities. We present a case initially diagnosed as an SMA dissection on CT, but upon detailed review of the imaging findings was considered to be incompletely f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The traditional approach describes piriformis syndrome as a neuromuscular disorder classified as compression neuropathy, caused by compression on the SN at the level of the PM [ 2 – 5 ]. However, there are some patients with abdominal pain of uncertain etiology (e.g., some anatomical variants of vasculature of the abdomen) that may lead to unnecessary investigation and intervention [ 6 ]. Piriformis syndrome poses a considerable diagnostic problem, and data on its etiopathogenesis, especially with regard to its anatomical conditions, are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional approach describes piriformis syndrome as a neuromuscular disorder classified as compression neuropathy, caused by compression on the SN at the level of the PM [ 2 – 5 ]. However, there are some patients with abdominal pain of uncertain etiology (e.g., some anatomical variants of vasculature of the abdomen) that may lead to unnecessary investigation and intervention [ 6 ]. Piriformis syndrome poses a considerable diagnostic problem, and data on its etiopathogenesis, especially with regard to its anatomical conditions, are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In their case, while the initial CT revealed an abnormal appearance of the SMA as dissection, further investigation of the abdominal aortal and visceral arteries showed a congenital anatomical variant. They concluded that understanding the embryological origin of the abdominal vasculature combining with radiological signs was important to distinguish variants from pathological findings [ 6 ]. As concomitant disorders or congenital anatomical variations may increase the risks of the surgery performed, the patient should be informed about the interventional carotid artery procedures (e.g.…”
Section: Discussionmentioning
confidence: 99%